The Raffles Museum, Singapore, 1823-1960 : performativities of British colonial rule - Ang, Eiselt Chin Siew (Nanyang Technological University, 2019)
This dissertation is an interdisciplinary, humanist-centered examination of the cultural biography of the Raffles Museum, the predecessor of three present-day Singapore museums. Established in 1823 by the proconsul of British Southeast Asia, Thomas Stamford Raffles, the Raffles Museum was a major center for Western natural history and anthropological research, as well as the collecting of and within Southeast Asia from the latter 1800s until the early 1900s. Its site, building, collections, and biography thus document simultaneously, the West in Asia, British colonial politics and strategies in Southeast Asia, as well as Singapore’s colonial experience. This thesis argues against an existing historical positioning of the museum as first, a benign repository; and second, as having been established by Raffles out of a colonial humanitarian dream and vision that was "inconsistent with the [imperial] realities of its time." It asserts that such a historical position makes no substantive calibration of crucial aspects of the museum’s institutional persona: as a Western institution that emerged out of the West, with Western methodologies and praxes, and that was deeply entangled in Western eighteenth/nineteenth-century colonization of the non-West. Most importantly, it ignores the larger questions of British imperial trade, its geopolitics, as well as Raffles’s ambitions vis-à-vis this trade. As a result, the Raffles Museum’s establishment and function as a British colonial technology of rule has not been completely and properly calibrated and its role in Singapore’s colonial experience has been misrepresented. By making close examinations of Raffles’s objectives and the "ongoing historical, political, moral relationships…" that were within the museum, this dissertation demonstrates that contra to such a position, Raffles’s establishment of the museum and British colonial utilization of the museum were exactly consistent with the imperial realities of the time. What follows is a corrective to such a reading of the Raffles Museum’s history, and by extension, Raffles’s political strategies and legacy, as well as Singapore’s colonial experience. §